Growth and Inflation Dispersions in EMU : Reasons, the Role of Adjustment Channels, and Policy Implications - Stavrev, Emil (IMF Working Papers; Working Paper ;, 2007)
This paper's analysis of growth and inflation dispersions in the euro area reveals several findings. First, these dispersions have declined appreciably since EMU; remaining dispersions are small but persistent, relating mainly to country-specific shocks, not differences in the transmission of common shocks. Second, the different behavior of interest rates just before and after the introduction of the euro has contributed significantly to growth dispersions. However, this has been a one-off shock whose effects, particularly on construction, should be declining over time. Third, financial sector integration could do much more to insure countries against shocks and increase consumption smoothing.